PSMD12 haploinsufficiency in a neurodevelopmental disorder with autistic features. Issue 8 (13th November 2018) - Khalil, Raida; Kenny, Connor; Hill, R. Sean; Mochida, Ganeshwaran H.; Nasir, Ramzi; Partlow, Jennifer N.; Barry, Brenda J.; Al‐Saffar, Muna; Egan, Chloe; Stevens, Christine R.; Gabriel, Stacey B.; Barkovich, A. James; et al.
Abstract: Protein homeostasis is tightly regulated by the ubiquitin proteasome pathway. Disruption of this pathway gives rise to a host of neurological disorders. Through whole exome sequencing (WES) in families with neurodevelopmental disorders, we identified mutations in PSMD12, a core component of the proteasome, underlying a neurodevelopmental disorder with intellectual disability (ID) and features of autism spectrum disorder (ASD). We performed WES on six affected siblings from a multiplex family with ID and autistic features, the affected father, and two unaffected mothers, and a trio from a simplex family with one affected child with ID and periventricular nodular heterotopia. We identified an inherited heterozygous nonsense mutation in PSMD12 (NM_002816: c.367C>T: p.R123X) in the multiplex family and a de novo nonsense mutation in the same gene (NM_002816: c.601C>T: p.R201X) in the simplex family. PSMD12 encodes a non‐ATPase regulatory subunit of the 26S proteasome. We confirm the association of PSMD12 with ID, present the first cases of inherited PSMD12 mutation, and demonstrate the heterogeneity of phenotypes associated with PSMD12 mutations.